Genç Yetişkinlerde Mutluluğun Özgünlük ve Kişisel Erdemler Açısından İncelenmesi - Aydın, Merve (Muş Alparslan Üniversitesi, 2018)
Buçalışmanın amacı genç yetişkinlerin mutluluğunu cinsiyet, özgünlük ve kişiselerdemler açısından incelemektir. Araştırmada ilişkisel tarama modelikullanılmıştır. Çalışma grubunu 18-25 yaş aralığında bulunan 198 genç yetişkinoluşturmaktadır. Araştırmada Oxford Mutluluk Ölçeği Kısa Formu, Özgünlük Ölçeğive Kişisel Erdemler Ölçeği kullanılmış, veriler SPSS 21 İstatistik Programı ileanaliz edilmiştir. Verilerin analizinde Mann Whitney U-testi, korelasyonanalizi ve çoklu regresyon analizi kullanılmıştır. Bulgulara göre gençyetişkinlerin mutluluk düzeyleri cinsiyete göre farklılaşmamaktadır. Mutlulukile özgünlük, sorumluluk, amaçlılık ve değerlilik özellikleri arasında pozitifyönde ve anlamlı ilişki saptanmıştır. Özgünlük, amaçlılık özelliği ve değerliliközelliği bir arada genç yetişkinlerin mutluluğunu % 45, 8 düzeyindeyordamaktadır.

Thepurpose of this study is the investigation of the happiness of the young adultsin terms of gender, authenticity and personal virtues. The correlativeinvestigation model was used in this research. A total of 198 participants whowere young adults between the ages of 18 and 25 were included in the study. Inthis research Short Form of the Oxford Happiness Questionnaire, AuthenticityScale and Personal Virtues Scale were used. The data were analyzed through theSPSS 21 statistical software. In the data analysis, the multiple regressionanalysis, the correlation analysis and Mann Whitney U-test have been used.According to results, happiness of the young adults do not differ according togender. Positivity and meaningful relationships were determined betweenhappiness and authenticity, responsibility, purposefulness, worthiness.According to the results of the regression analysis, it was found thatauthenticity, purposefulness and worthiness highly (45.8 %) predicted to happinessof the young adults.
The Investigation of the Happiness of the Young Adults in Terms of Authenticity and Personal Virtues
anemon
Keywords: Genç Yetişkin; Mutluluk; Özgünlük; Kişisel Erdemler; Young Adult; Happiness; Authenticity; Personal Virtues